BETON NON PASIR DENGAN AGREGAT DARI BATU ALAM (BATU APE) SUNGAI LUA KABUPATEN KEPULAUAN TALAUD SULAWESI UTARA - Trisnoyuwono, Diarto; Tjokrodimuljo, Kardiyono; Satyarno, Iman (Civil Engineering Forum Teknik Sipil, 2009)
Timber supply is diminishing in addition to the trend to lower quality but higher cost of wood production manufacturing. However, because the demand of this material continues, an alternative or substitution on the use of timber, such as bamboo laminated, is desirable. Having susceptible character to powder by beetles attack, bamboo must be passed through preservation process before it is applied as laminating materials, but chemical preservative materials used in industrial process ring negative impacts to the environment. One of human and environmental friendly preservatives is the tobacco extract. Nevertheless, the most effective concentration of tobacco extract and its influence to the adhesive materials have not been well recognized. This research objective was to investigate the influence of tobacco extract to the natural and mechanic behaviour of laminated bamboo. Dried tobacco flake was mixed with water in variable concentration of 100, 125, 150 and 175 gram/liter. Bamboo split were given treatment in boiling water with tobacco extract solutions. As benchmarking, bamboo split also preserved with boiling water (without preservatives materials) and 5% concentration of borax. Non preservative bamboo was used as the control. The result of experiment showed that 150 gram/liter tobacco extract concentration of caused 61,33% insect mortality and 1,87% decreased weigh, which is effective to be used as preservative in compare to other three concentrations. Water content and density observation showed that preservation using 150 gram/liter extract tobacco comparing to non preservative boiling preservation, produced smaller value of water content and larger value of density than borax preservative. Preservation using 150 gram/liter tobacco extract produced highest value of compression parallel to grain and modulus of the bamboo elasticity Petung mechanic properties were 277,95 MPa and 170,34 MPa, respectively. Mechanical properties of laminated bamboo that were significantly influenced by preservative variation showed that highest values for compression parallel to grain and modulus of elasticity were 66,09 MPa and 127,12 MPa, respectively and reached by preservation using 100 gram/liter of tobacco extract.